Adult education and training for the development of problem-solving skills - I. A. Korshunov; S. V. Lubnikov; N. N. Shirkova (Образование и наука)
Introduction. Currently, the presence of employees with developed basic skills of working with textual and numerical information can no longer explain how effectively a person functions in society and the professional sphere. This is due to the rapid transformation of the innovative economy and the renewal of production technologies and business processes. Therefore, the key basic skills of the adult population have been supplemented with one more cognitive skill – problem solving.   Aim. The present research aimed to present a portrait of a person with a developed problem-solving skill on the basis of sociological data, and to identify which types of employee training could most effectively lead to his/her development during participation in educational activities.   Materials and methods. The study was based on theoretical methods of literature analysis, which made it possible to describe the categorical field and to systematize existing scientific approaches. The empirical foundation for this research was built on the data of OECD-PIAAC studies in Russia (2013). The study sample consisted of 3,877 people employed in various sectors of economic activity. To process the results obtained, the authors used the methods of mathematical statistics (descriptive statistics, one-factor analysis of variance, regression analysis method).   Results. It was discovered that even prolonged employer-provided training does not lead to development of problem-solving skills, but still provides an increase in salary for some workers. Moreover, training which is not directly connected to the professional field and not initiated by the employer would lead to increase in problem-solving skills in a technology-rich environment. In this study, it is debated that the most significant increase in problem solving skills was brought by informal on-the-job training. It was shown that problem-solving skills provide significant increase in labour productivity in the production fields and intellectual labour fields (education and science). At the same time, problem-solving skills barely provide any increase in labour productivity in the routine fields, because such type of jobs does not involve behavioural variability, operational problem solving, and constant cooperation with other people.   Scientific novelty. For the first time in the Russian academic literature, the authors conceptualised the concept of problem-solving skills and clarified which types of training significantly increase the contribution to the development of human capital of Russian workers. Based on the results of the study the authors presented a sociological portrait of a Russian worker with a high and low level of problem-solving skills. The revealed patterns allowed the authors to form an idea of the system of organisational conditions of enterprises that ensure maximum involvement of employees in the constant updating of their knowledge and skills, and contribute to the effective use of the problems-solving skill in the process of labour activity.   Practical significance. This article might be of interest for the specialists in sphere of adult education and lifelong learning, HR-specialists and small and medium-sized enterprise managers in order to improve the efficiency of the recruitment process and to adopt more efficient employer-provided training systems.